2021
DOI: 10.3390/nu13082632
|View full text |Cite
|
Sign up to set email alerts
|

Does Sodium Intake Induce Systemic Inflammatory Response? A Systematic Review and Meta-Analysis of Randomized Studies in Humans

Abstract: Experimental studies suggest that sodium induced inflammation might be another missing link leading to atherosclerosis. To test the hypothesis that high daily sodium intake induces systemic inflammatory response in humans, we performed a systematic review according to PRISMA guidelines of randomized controlled trials (RCTs) that examined the effect of high versus low sodium dose (HSD vs. LSD), as defined per study, on plasma circulating inflammatory biomarkers. Eight RCTs that examined CRP, TNF-a and IL-6 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…Several cross-sectional studies associated a higher salt intake with higher CRP levels in adults and elderly people [ 70 , 71 ], although this association was not found in adolescents [ 72 ]. A recent meta-analysis also found no associations between dietary sodium level and markers of inflammation, although it should be noted that the researchers pointed out that their findings were likely due to methodological errors [ 73 ].…”
Section: Possible Mechanisms Explaining the Relationship Between Upf ...mentioning
confidence: 99%
“…Several cross-sectional studies associated a higher salt intake with higher CRP levels in adults and elderly people [ 70 , 71 ], although this association was not found in adolescents [ 72 ]. A recent meta-analysis also found no associations between dietary sodium level and markers of inflammation, although it should be noted that the researchers pointed out that their findings were likely due to methodological errors [ 73 ].…”
Section: Possible Mechanisms Explaining the Relationship Between Upf ...mentioning
confidence: 99%
“…Persistent smoldering inflammation causes an enhanced release of reactive oxygen and nitrogen species, resulting in DNA damage and pro-oncogenic transcription factor dysregulation, leading to tumorigenesis, proliferation, and metastasis [ 3 ]. High salt (sodium chloride, NaCl) is a well-known mediator of chronic inflammation [ 4 ]. Previous studies in our laboratory have demonstrated that murine breast tumors, compared to the surrounding soft tissue, accumulate 30–70% higher sodium content [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the concentration of folic acid should be often evaluated in patients with IBD and given as a supplement in cases of insufficient dietary intake and/or absorption [ 5 ]. Basdeki et al performed a systematic review and meta-analysis of previously published randomized controlled trials (RCTs) investigating the relationship of sodium intake with systemic inflammation [ 6 ]. Although the study did not verify the hypothesis that sodium intake can induce a systemic inflammatory response in humans in a dose–response manner, it highlighted major issues that could be addressed in future relevant RCTs [ 6 ].…”
mentioning
confidence: 99%
“…Basdeki et al performed a systematic review and meta-analysis of previously published randomized controlled trials (RCTs) investigating the relationship of sodium intake with systemic inflammation [ 6 ]. Although the study did not verify the hypothesis that sodium intake can induce a systemic inflammatory response in humans in a dose–response manner, it highlighted major issues that could be addressed in future relevant RCTs [ 6 ]. In a systematic review, Tsiogkas et al summarized the current evidence regarding the efficacy of Crocus sativus (Saffron) supplementation in patients with rheumatic diseases (RDs) [ 7 ].…”
mentioning
confidence: 99%